Answer:
1/6
Step-by-step explanation:
Step-by-step explanation:
a) 6-9b=3a
First:Subtract
3b=3a
Second: Devide
3b/3a
=(3÷3)(b÷a)
=1b/a
= b/a
B) 6b+2a=3a
First:Transpose (Group the like terms. signs will change.)
-3a+2a=-6b
=-1a=-6b
Second:Divide
=-1a/-6b:(-1÷-6)(a÷b)
=1a/6b
=a/6b
C)a/3=b+2
First: Transpose
a=3+2+b
=a/6+b
Answer: 1 over 12
Step-by-step explanation:
Answer:
Step-by-step explanation:
X^2-6x+5=x^2-5x-x+5=x(x-5)-(x-5)=(x-5)(x-1)
Then we have (x-5)(x-1)=0 if x=5 or x=1.
Intersections on x are points (1,0) and (5,0), middle is (3,0).
Intersection with y is when put x=0 in equation, so you will get y=0-6*0+5, y=5. The point is (0,5).
From picture symmetry is line x=3.